Citizen satisfaction with public goods and government services in the global urban south: A case study of Cali, Colombia (2015)
In this paper we present data from a recent survey of residents' satisfaction levels with a range of urban public goods and government performance in Cali, Colombia. The more affluent report higher levels of satisfaction, especially with regard to security, public space, utilities and government performance, compared to the poor. The low scoring on satisfaction with civic norms and government performance, especially amongst the poor, undermines the notion of an aspirations paradox, suggests a lack of social capital and distrust of government, and indicates a social capital deficit. Our survey results indicate that strengthening the bonds of social capital, improving urban public space and working to improve public safety should be important areas of concern for urban and national governments.